Huckleberry Finn - Twain, Mark (Nxb. Đồng Nai, 2009)
Huckleberry Finn had a tough life with his drunk father until an adventure with Tom Sawyer changed everything. But when Huck's dad returns and kidnaps him, he must escape down the Mississippi river with runaway slave, Jim. They encounter trouble at every turn, from floods and gunfights to armed bandits and the long arm of the law. Through it all the friends stick together - but can Huck and Tom free Jim from slavery once and for all?